Welcome to an Action Against Mental Colonialism - Mishra, A.K. (Intellectual Journal of Academic Research, 2023)
This editorial introduces the inaugural issue of the Intellectual Journal of Academic Research (IJAR), which aims at covering the uncovered in Nepali and English language focusing quality contents across social science. It starts with a background to Mental Colonialism, highlights the justification of names and needs of this journal. Acknowledging the individuals and institutions involved in bringing the journal from its conception to fruition, the editorial ends with a call on researchers and practitioners to cross over Mental Colonialism and create an intellectual platform for social science exchange that can lead to positive change in the society. Institutional pressure is general strongest at research universities. The pressure to publish has been observed as a cause of poor work being submitted to academic journals and publishing in ranked factors journals by paying caused to create financial burden to developing countries authors. While the where of publishing is important, it is more important to focus on what is published. Getting published for scholars in poor countries can be difficult due to cost of publication, language barriers, lack of resources, discrimination and limited access to information. IJAR Journal is introduced to create an equal opportunity through open access without any charge after blind peer review. In 21st century anything from anywhere, it is easy for digitization after which the power of your knowledge and innovation decide further moves